2020
DOI: 10.1021/acsphotonics.0c00878
|View full text |Cite
|
Sign up to set email alerts
|

Postpassivation of Multication Perovskite with Rubidium Butyrate

Abstract: Many multication perovskites for highly stable and efficient solar cells benefit from rubidium iodide introduced in the precursor solution. It is well known that Rb + influences positively the optoelectronic and mobility properties and has a direct effect upon crystallization and halide homogenization. As Rb + is often incorporated by adding RbI in the precursor solution, it can be difficult to distinguish the influence of Rb + and Iseparately.Herein, we report a post-passivation of methylammonium-free (CsFA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…For example, recently Nogueira and co‐workers reported that Rb + binds to interstitial halogen (I i and Br i ) defects at the grain boundaries, resulting in a reduced deep traps density by the formation of shallower states. [ 52 ] In addition, theoretical research also demonstrated that the deep traps can be reduced by alkali metals in contact with interstitial halide defects. [ 53 ] For these reasons, we conclude that the decreased trap density should be attributed to the Rb + cations, including those locating at the interface and in the bulk perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recently Nogueira and co‐workers reported that Rb + binds to interstitial halogen (I i and Br i ) defects at the grain boundaries, resulting in a reduced deep traps density by the formation of shallower states. [ 52 ] In addition, theoretical research also demonstrated that the deep traps can be reduced by alkali metals in contact with interstitial halide defects. [ 53 ] For these reasons, we conclude that the decreased trap density should be attributed to the Rb + cations, including those locating at the interface and in the bulk perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…Alkali metal cations might also be explored to assist in the passivation of defects in both A and A' sites. Our group developed a post‐synthetic method of passivation that might be suitable to passivate 2D‐PSCs: the use of rubidium butyrate as a passivating agent may effectively passivate both cation vacancies (V A and V A’ ) and surface halide vacancies (V X ) 208 . Another advantage in using this passivation method is that the organic acylate can be chosen to match the aryl/alkylammonium backbone of the separators (e.g., butyrate/butylammonium), so that its introduction when passivating halides vacancies would be less disturbing to the crystal structure.…”
Section: Perspectivesmentioning
confidence: 99%
“…[ 18,19 ] However, the full elimination of MA + must be targeted for a better stabilization. [ 20–33 ] The most popular approach for MA‐free PSCs consists in replacing MA + by Cs + and/or by Rb + cations, two alkali metals. [ 20,21,31–33 ] Several authors have developed interfacial engineering for boosting the performances of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20,21,31–33 ] Several authors have developed interfacial engineering for boosting the performances of the devices. [ 22–24,33 ] However, in the absence of MA, PSCs usually show inferior PCEs due to an insufficient quality of the PVK material. Increasing the material crystallinity and passivating defects must be targeted.…”
Section: Introductionmentioning
confidence: 99%